From "Gazing" to "Defining": Li Jiaqi's Identity as the "Feminist Man" Spokesperson and the Reconstruction of Gender Discourse - Xing, Mingzi; Gao, Yan (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
In recent years, male endorsements for women's products have become a new marketing strategy in China's consumer market. The rise of Li Jiaqi, the "King of Lipsticks", is a typical example of this phenomenon. This article combines the gaze theory, post-feminism, masculinity research, gender manipulation theory and Bourdiere's symbolic violence theory to deeply analyze the construction logic, power relations and influence on gender discourse of Li Jiaqi as the spokesperson of "feminist men". Research has found that Li Jiaqi, through the discourse construction of "all girls", ingeniously bound the consumption of female goods with the discourse of gender equality, achieving a transformation from "the man being gazed at" to "the gaze medium", while simultaneously triggering widespread controversy over "pseudo-feminist" marketing. This study not only expands the connotations of feminist theory and gaze theory, but also provides practical guidance for gender equality in commercial communication.